Transformative Photography: Evaluation and Best Practices for Eliciting Social and Policy Changes. (April 2013) - Ozanne, Julie L.; Moscato, Emily M.; Kunkel, Danylle R.
Marketing researchers commonly use photographic methods to generate observational data and delve into the lived experiences of research participants. These visual data-gathering techniques, however, can be embedded into a broader research methodology aimed to generate constructive social and policy changes. The authors systematically analyze prior empirical studies using photographic methods to identify when these methods are appropriate and most effective. They identify key research processes, workbench issues, and ethical dilemmas when employing transformative photographic methods across individual, group, and community levels of analysis. Finally, they propose best practices for conducting more compelling research.